Complications of Regional Anesthesia Principles of Safe Practice in Local and Regional Anesthesia - Finucane, Brendan T.; Tsui, Ban C.H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Reflecting the rapid growth of pain medicine and of ultrasound as a tool, this Third Edition is more comprehensive and inclusive than previous editions and features additional pages, tables, diagrams, and color illustrations. In addition to the discipline of Anesthesiology, other specialists, who use local and regional anesthesia techniques, (surgeons, ophthalmologists, emergency medicine physicians and dentists), have also contributed to this edition of the book. Complications of Regional Anesthesia, with its newly added subtitle, Principles of Safe Practice in Local and Regional Anesthesia, stresses the relatively new emphasis and importance on safety and prevention and broadens the discussion to include the practice and administration of not just regional but also local anesthesia. Each chapter has been thoroughly revised, brought up-to-date, and features full color images. Individual chapters cover complications associated with specific nerve blocks; IV and catheter methods; obstetric regional anesthesia; pediatric regional anesthesia; ophthalmic regional anesthesia; and treatment of acute and chronic pain.
Section I. General Considerations -- 1.The History of Local and Regional Anesthesia -- 2.Regional Anesthesia Safety -- 3.Local Anesthetic Toxicity: Prevention and Management -- 4.Outcome Studies Comparing Regional and General Anesthesia -- Section II. Special Considerations -- 5.Nerve Injury Resulting from Intraneural Injection When Performing Peripheral Nerve Block -- 6.Regional Anesthesia in the Presence of Neurological Disease -- 7.Evaluation of Neurologic Injury Following Regional Anesthesia -- 8.Regional Anesthesia and Anticoagulation -- 9.Infection in Association with Local and Regional Anesthesia -- 10.Continuous Peripheral Nerve Blocks Safe Practice and Management -- Section III. Specific Regional Blocks-Safe Practice and Management of Adverse Events -- 11.Complications of Regional Anesthesia: Upper and Lower Extremity Blockade -- 12.Complications of Thoracic Wall Regional Anesthesia and Analgesia -- 13.Abdominal Wall Blocks: Safe Practice and Management of Adverse Events -- 14.Epidural Blockade: Safe Practice and Management of Adverse Events -- 15.Spinal Anesthesia: Safe Practice and Management of Adverse Events -- Section IV. Specific Patient Populations-Safe Practice and Management of Adverse events -- 16.Complications of Regional Anesthesia in Chronic Pain Therapy -- 17.Local and Regional Anesthesia in the Elderly -- 18.Local and Regional Analgesia for Labor and Delivery -- 19.Local and Regional Anesthesia in Obese Patients -- 20.Local and Regional Anesthesia in Pediatrics -- Section V. Special Environments: Safe Practice and Management of Adverse Events -- 21.Local and Regional Anesthesia in Dental and Oral Surgery -- 22.Local and Regional Anesthesia in the Emergency Room -- 23.Recognizing and Mitigating Risk of Ophthalmic Regional Anesthesia -- 24.Local Infiltration Analgesia for Orthopedic Joint Surgery -- 25.Local and Regional Anesthesia in Plastic Surgery: Safety Considerations and Management -- Section VI. Morbidity Studies: International Perspective -- 26.Development and Methodology of a Registry of Regional Anesthesia -- 27.Australia: Results of a Multi-Center Registry of Regional Anesthesia -- 28.Canada: Medical Legal Aspects of Regional Anesthesia Practice -- 29.France: Regional Anesthesia Morbidity Study -- 30.Nordic Countries: Principles of Safe Practice in Local and Regional Anesthesia -- 31.United Kingdom: Recent Advances in the Safety and Prevention of Regional Anesthesia Complications -- 32.United States: Complications Associated with Regional Anesthesia (An American Society of Anesthesiologists$1 (BClosed Claims Analysis) -- 33.United States: Chronic Pain Management (American Society of Anesthesiologists$1 (BClosed Claims Project) -- Section VII. Medical Legal Aspects -- 34.Medical Legal Aspects of Regional Anesthesia: Physician Perspective -- 35.Medical Legal Aspects of Regional Anesthesia: Legal Perspective.s
Keywords: Medicine; Anesthesiology; Pain medicine; Medicine & Public Health; Anesthesiology; Pain medicine